Arbitration of Two-party Disputes under Uncertainty - Rosenthal, R. W. (Review of Economic Studies, 1978)
Journal Article Arbitration of Two-party Disputes under Uncertainty Get access Robert W. Rosenthal Robert W. Rosenthal Bell Telephone Laboratories, Inc. Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 3, October 1978, Pages 595–604, https://doi.org/10.2307/2297260 Published: 01 October 1978 Article history Received: 01 September 1976 Accepted: 01 June 1977 Published: 01 October 1978